From Sectarianism to Scientific Naturalism? Rethinking Madhhab-Based Differences in the Exegesis of Q.S. Al-Maidah: 6 - Muhammad Nurul Widad; Fadhil Achmad Agus Bahari; Isyak Isyak; Moh. Ikhya Ulumuddin Al Hikam (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
This study examines the interpretive differences in classical Quranic legal exegesis, which are often perceived as expressions of sectarian bias. Focusing on the interpretation of Q.S. al-Maidah [5]:6, the article aims to reassess whether madhhab-based differences reflect ideological division or epistemic variation. Using a qualitative, library-based approach, this study analyzes four major works of Ahkam al-Quran—by al-Jassas (Hanafi), al-Kiya al-Harrasi (Shafii), Ibn al-Arabi (Maliki), and Ibn al-Jawzi (Hanbali). The analysis employs Ibn Taymiyyah’s framework of Ikhtilaf al-Mufassirin to classify types of interpretive differences, complemented by a discursive perspective inspired by power-knowledge analysis. The findings show that most differences among the exegetes fall within ikhtilaf tanawwu (legitimate variation), rather than contradiction. These variations arise from linguistic interpretation, juristic reasoning, and methodological commitments, not from sectarian motives. This study argues that such diversity can be understood as a scientific naturalism of tafsir, in which interpretive plurality emerges naturally from the internal dynamics of the Quranic text and the intellectual frameworks of the mufasir. This perspective contributes to Quranic studies by reframing madhhab-based differences as a form of disciplined epistemic diversity rather than ideological conflict, thereby offering a more balanced understanding of classical tafsir.